Quality assessment of selected groundwater sources in Brgy. San Fernando, Miagao, Iloilo - Nerpiol, Evan Jude Pagapulan (2005.)
The quality of the selected groundwater sources in Brgy. San Fernando, Miagao, Iloilo was assessed.
Sotech thesis.
Keywords: Groundwater; Quality assessment; Brgy. San Fernando, Miagao, Iloilo